2000
DOI: 10.1074/jbc.m907881199
|View full text |Cite
|
Sign up to set email alerts
|

The α, but Not the β, Isoform of the Human Thromboxane A2 Receptor Is a Target for Prostacyclin-mediated Desensitization

Abstract: In this study, we examined the effects the prostacyclin receptor (IP) agonist cicaprost exhibited on U46619-mediated thromboxane A 2 receptor (TP) signaling in platelets and compared it to that which occurs in human embryonic kidney (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
154
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(175 citation statements)
references
References 81 publications
20
154
1
Order By: Relevance
“…Figure 5D]. Subsequent, whole cell phosphorylation assays confirmed that TPα, but not TPβ or TPα S329A , is indeed a direct target of cicaprost / IPmediated PKA phosphorylation [62]. Thus, these studies confirm that TPα, but not TPβ, is subject to counter regulation or heterologous desensitization by IP, mediated through direct PKA phosphorylation within the unique C-tail of TPα whereby Ser 329 has been identified as the target residue for phosphorylation.…”
Section: Tp Receptor Desensitizationmentioning
confidence: 65%
See 1 more Smart Citation
“…Figure 5D]. Subsequent, whole cell phosphorylation assays confirmed that TPα, but not TPβ or TPα S329A , is indeed a direct target of cicaprost / IPmediated PKA phosphorylation [62]. Thus, these studies confirm that TPα, but not TPβ, is subject to counter regulation or heterologous desensitization by IP, mediated through direct PKA phosphorylation within the unique C-tail of TPα whereby Ser 329 has been identified as the target residue for phosphorylation.…”
Section: Tp Receptor Desensitizationmentioning
confidence: 65%
“…Computational analyses of the unique C-tail domains of the TPα isoform indicated the presence of a putative PKA phosphorylation site within the sequence RS 329 LSL where Ser 329 is predicted to be the target residue for phosphorylation [62]. Figure 5D].…”
Section: Tp Receptor Desensitizationmentioning
confidence: 99%
“…i ) was assessed in stably transfected HEK cells, as previously described [14]. Cells were loaded for 1h at 37 o C with 5uM Fura-2/AM (Molecular Probes) in phenol red free-RPMI 1640 culture media.…”
Section: Intracellular Calcium (Ca 2+mentioning
confidence: 99%
“…More recent reports show that both TPα and TPβ are subject to differential heterologous desensitization. For instance TPα, but not TPβ, is subject to cross-desensitization by prostacyclin, mediated through direct protein kinase (PK) A phosphorylation of TPα at Ser 329 ; these latter findings led to the proposal that TPα may be the isoform physiologically relevant to TP:prostacyclin receptor (IP)-mediated vascular hemostasis (8). Furthermore TPα, but not TPβ, is subject to prostaglandin (PG) D 2 receptor (DP)-mediated cross desensitization (9).…”
Section: Discussionmentioning
confidence: 99%